Effect and impact of mechanical ventilation in myotonic dystrophy type 1: a prospective cohort study. Issue 11 (23rd March 2018) - Boussaïd, Ghilas; Prigent, Hélène; Laforet, Pascal; Raphaël, Jean-Claude; Annane, Djillali; Orlikowski, David; Lofaso, Frédéric
Abstract : Few studies have assessed the impact of home ventilation in patients with myotonic dystrophy type 1 (DM1) and no specific recommendations are available. We assessed the survival associated with category of home ventilation adherence of patients with DM1 followed up at a home ventilation unit using a Cox proportional hazards model. 218 patients were included; those who refused or delayed their acceptance of non-invasive ventilation were at higher risk for severe events (invasive ventilation or death) (P=0.03). Risk of death was associated with orthopnoea (HR 2.37; 95% CI 1.17 to 4.80; P<0.02) and adherence category (100 to 90% vs >75%: HR 3.26; 95% CI 1.32 to 8.04; P<0.03). Failure to use home ventilation as prescribed may be associated with increased mortality in patients with DM1.